PENGARUH PEMBELAJARAN PENEMUAN TERBIMBING PADA TIPE SISWA FIELD DEPENDENT – INDEPENDENT TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMP - Saesmita, Carolina (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
This study aims to determine: (1) Differences in mathematics achievement between groups of students who are taught by learning guided discovery and learning achievement in mathematics group of students who are taught by conventional teaching (2) Differences in mathematics achievement between groups of students and field independent with mathematics achievement groups of students and field dependent on the use of guided discovery learning (3) the difference in mathematics achievement between groups of students who are dependent field with mathematics learning achievement of students whose field independent groups in the use of conventional learning.This study is a quasi-experimental quantitative research. The research was conducted in the second semester of 2012/2013 academic year at St. Joseph's SMPK Madison with a population of class VII. While the sample is a class VII B as a class experiment using guided discovery learning and class as a class VII C control with conventional learning. The data collection technique using the test method. Instrument used in the test method is the mathematics achievement test and test GEFT. Mathematics achievement test used to determine students' mathematics achievement while tests are used to determine students GEFT Field Dependent - Independent.From the research and statistical analysis was obtained: (1) there are differences in mathematics achievement of students with learning guided discovery and achievement of mathematics learning with conventional learning, (2) there was no difference in mathematics achievement of students field independent and mathematics achievement of students field dependent on the use of guided discovery learning, and (3) there was no difference in learning achievement of student mathematics achievement field dependent and field independent students' mathematics learning in the use of conventional learning.Keywords: Mathematics Learning Achievement, Student Field Dependent - Independent, Guided Invention